Comparação biológica, morfológica e molecular entre carrapatos do complexo Rhipicephalus sanguineus (Acari: Ixodidae) - Sanches, Gustavo Seron [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The present study compares biological, morphological and molecular aspects of the adult stage of Rhipicephalus sanguineus ticks from different geographical regions of the world, such as Cuba (Havana), Brazil (Jaboticabal), Thailand (Bangkok), Argentina (Rafaela), and R. turanicus from Spain (Zaragoza). Furthermore, for R. sanguineus from Brazil (Jaboticabal) and R. turanicus from Spain (Zaragoza) the biological comparison were made for the immature stages, as well as the crossbreeding between these tick species. The larval stage of R. turanicus from Spain (Zaragoza) showed lower weight after feeding on rabbits when compared with R. sanguineus from Brazil (Jaboticabal). However, R. turanicus from Spain (Zaragoza) showed larger nymphs and adults due to a higher rate of growth, facilitated by greater intake of blood of these stages in relation to the R. sanguineus from Brazil (Jaboticabal). The crossbreeding between R. sanguineus from Brazil (Jaboticabal) and R. turanicus from Spain (Zaragoza) was not successful since the females crossed transpecifically produced a small amount of infertile eggs, indicating a separation between these two species. The comparison of biological parameters for the adult stage of the different populations showed differences, mainly in the weight of engorged females and in the engorgement period, also reflecting on the morphometric parameters of these species. The morphometric analysis suggests major similarity between R. sanguineus from Argentina (Rafaela) with R. turanicus from Spain (Zaragoza), also showing variations of size relative to populations of R. sanguineus from Cuba (Havana), Brazil (Jaboticabal) and Thailand (Bangkok). Morphologically, some differences were observed, especially in relation to the idiosoma shape, basis capituli shape and posterolatetal angles, females’ genital aperture and males’ spiracular plates, suggesting the occurrence of polymorphisms in different populations of R...

O presente estudo apresenta a comparação biológica, morfológica e molecular do estágio adulto de carrapatos Rhipicephalus sanguineus de diferentes regiões geográficas: Cuba (Havana), Brasil (Jaboticabal), Tailândia (Bangkok), Argentina (Rafaela) e também do R. turanicus da Espanha (Zaragoza). Além disso, para o R. sanguineus do Brasil (Jaboticabal) e R. turanicus da Espanha (Zaragoza) foram realizadas comparações biológicas dos estágios imaturos, assim como o cruzamento entre estas espécies. O estágio larval de R. turanicus da Espanha (Zaragoza) apresentou menor peso após o ingurgitamento em coelhos, quando comparado com o estágio larval de R. sanguineus do Brasil (Jaboticabal). Entretanto, R. turanicus da Espanha (Zaragoza) apresentou ninfas e adultos maiores devido a uma maior taxa de crescimento, facilitada pela maior ingestão de sangue destes estágios em relação ao R. sanguineus do Brasil (Jaboticabal). Os cruzamentos entre R. sanguineus do Brasil (Jaboticabal) e R. turanicus da Espanha (Zaragoza) não foram bem sucedidos, uma vez que as fêmeas cruzadas transpecificamente produziram uma pequena quantidade de ovos, que eram inférteis, indicando uma separação entre estas duas espécies. A comparação dos parâmetros biológicos para os estágios adultos das diferentes populações mostraram diferenças, principalmente no peso da fêmea ingurgitada e no período de ingurgitamento, refletindo também nos parâmetros morfométricos destas espécies. A análise morfométrica sugere maior semelhança entre R. sanguineus da Argentina (Rafaela) com o R. turanicus da Espanha (Zaragoza), mostrando também variações de tamanho em relação às populações de R. sanguineus de Cuba (Havana), Brasil (Jaboticabal) e Tailândia (Bangkok). Morfologicamente, algumas diferenças são observadas, principalmente em relação ao formato do idiossoma, formato da base do capítulo e ângulos póstero-laterais, abertura genital das fêmeas...
Keywords: Mites; Ácaro; Carrapato; Carrapato - Distribuição geográfica; Anatomia comparada; Morfologia (Animais)